OP19 Comparative Effectiveness Of Common Treatment Options For Benign Prostatic Hyperplasia: A Systematic Review And Network Meta-Analysis - Rojanasarot, Sirikan; Neeser, Kurt; Fu, Shuai; Bhattacharyya, Samir; McVary, Kevin (International journal of technology assessment in health care, 2022)
IntroductionTreatment options for men with moderate-to-severe lower urinary tract symptoms due to benign prostatic hyperplasia (BPH) include medical therapy, minimally invasive surgical therapies (MISTs), and invasive surgical procedures. While these treatments are recommended by American Urological Association Guidelines, they have different clinical profiles impacting both efficacy and durability outcomes. Using an indirect comparison approach, this study assessed the clinical effects of combination therapy (CT) using alpha-blockers and 5-alpha reductase inhibitors, two emerging MISTs (prostatic urethral lift [PUL] and water vapor thermal therapy [WVTT]), and two invasive surgical procedures (photoselective vaporization of the prostate [PVP] and transurethral resection of the prostate [TURP]).MethodsA systematic search of Medline, Embase, Cochrane Library, and relevant health technology assessment (HTA) databases was conducted to identify randomized and non-randomized clinical trials of the five treatments published prior to December 2020. Trials were included if they reported changes in International Prostate Symptom Score (IPSS) and retreatment rates, without any country or language restrictions. A random-effects network meta-analysis (NMA) with an aggregate regression model was performed to account for the baseline BPH severity and characteristic differences among men from the different trials.ResultsA total of 237 of 3,104 retrieved abstracts were included for full-text review. Of these, 16 randomized and four non-randomized clinical trials were included in the NMA. The random-effects NMA showed among medical and minimally invasive therapies, WVTT had the greatest one-year IPSS improvement (-∆11.7), followed by PUL (-∆10.4) and CT (-∆10.3). The one-year IPSS improvement for TURP and PVP was comparable (-∆14.1 vs. -∆13.8, respectively; p-value=0.675). The one-year retreatment rates were lowest for WVTT (3.0%), followed by CT (3.6%), TURP (6.3%), PVP (7.8%), and PUL (8.0%).ConclusionsWVTT provided greater clinical and durability benefits compared to other less invasive treatment options for men with BPH. Given NMA is increasingly used in HTA processes, this study provided systematically synthesized evidence that could facilitate decision-makers in determining new technology coverage decisions globally.